2018
DOI: 10.1108/intr-11-2016-0353
|View full text |Cite
|
Sign up to set email alerts
|

Individualism and internet addiction: the mediating role of psychological needs

Abstract: Purpose The purpose of this paper is to investigate the mediating role of psychological needs in the association between individualism and internet addiction. Design/methodology/approach A mixed-method design was used by comprising of 602 college students’ (70.3 percent women) responses obtained through the Individualism-Collectivism Survey, New Needs Assessment Questionnaire, and Internet Addiction Scale. Structural equation modeling techniques were used to investigate the theoretical relationships among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 87 publications
2
22
0
1
Order By: Relevance
“…Western countries, such as the American and European countries, are often perceived as having a more individualistic culture than the Southeast Asian countries [41,42]. Interestingly, Arpaci et al [43] found that a higher level of individualism, manifested by increased needs for achievement, autonomy, and dominance, and reduced need for affiliation, was significantly associated with a lower degree of Internet addiction. Accordingly, this higher level of individualism may have accounted for the lower prevalence of Internet and gaming disorders in Western countries than in Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Western countries, such as the American and European countries, are often perceived as having a more individualistic culture than the Southeast Asian countries [41,42]. Interestingly, Arpaci et al [43] found that a higher level of individualism, manifested by increased needs for achievement, autonomy, and dominance, and reduced need for affiliation, was significantly associated with a lower degree of Internet addiction. Accordingly, this higher level of individualism may have accounted for the lower prevalence of Internet and gaming disorders in Western countries than in Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Such drives for achievements and ranking are facilitated and fed in gaming contexts, structure, and progress, and therefore, might further increase gaming engagement and in turn increase IGD risk. This might be of higher importance among more VI-orientated inattentive gamers, who may be less able to achieve and compete in their real lives due to their inattention (Arpaci, Kesici, & Baloglu, 2017;Lee & Wohn, 2012;Stetina et al, 2011). Furthermore, individual autonomy and independence, related to higher VI tendencies, have been proposed as increasing the risk of developing IGD (Lee & Kim, 2015;Triandis, 1996).…”
Section: The Role Of VI In the Association Between Inattention And Igdmentioning
confidence: 99%
“…For instance, individualism or collectivism significantly affects the acceptance of mobile commerce (Faqih & Jaradat, 2015). Also, individualism culture affects internet addiction significantly (Arpaci, Kesici, & Baloğlu, 2018;Jiang, Li, & Shypenka, 2018).…”
Section: N P R E S Smentioning
confidence: 99%